A study of maternal and perinatal outcomes due to excessive maternal gestational weight gain in a district hospital in West Bengal – A cross-sectional study - Alina Bhattacharjee; Suresh Chandra Mondal; Mainak Chatterjee (Asian Journal of Medical Sciences, 2024)
Background: The weight gain that occurs in pregnancy has the potential to influence a woman’s long-term health by increasing the risk for weight retention and obesity, as well as related comorbidities such as chronic hypertension (HTN) or Type 2 diabetes mellitus. Aims and Objectives: The aim of the study was to study maternal and perinatal outcomes associated with excessive maternal gestational weight gain (GWG). Materials and Methods: The current study was a cross-sectional study conducted at the Department of Obstetrics and Gynecology, from October 2018 to October 2019. A total of 91 women attending the antenatal clinic of MR Bangur Hospital and getting admitted for delivery during the study period was considered as the study population. Medical records were maintained for variables of the mothers such as gestational diabetes mellitus (GDM), gestational HTN, pre-eclampsia, eclampsia, duration of labor, mode of delivery, indication of cesarean section, Postpartum hemorrhage, and perineal tears. coGuide v.0.01 used for statistical analysis. Results: There were majority of 55 (60.4%) participants reported 18.5–24.9 body mass index (BMI). The difference in the proportion of BMI across maternal weight gain was statistically significant. The difference in the proportion of GDM, duration of labor >18 h, and duration of the second stage of labor >2 h between maternal weight gain were statistically significant. The difference in the proportion of APGAR score at 1 min, and 5 min between groups of maternal weight gain was statistically significant. Conclusion: Our study suggested that GWG has to be achieved within the Institute of Medicine recommendation according to pre-pregnancy BMI to improve pregnancy outcomes and reduce maternal and perinatal adverse outcomes.